2017
DOI: 10.1186/s12913-017-2075-9
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods needs assessment of adult diabetes mellitus (type II) and hypertension care in Toledo, Belize

Abstract: BackgroundNon-communicable diseases, including diabetes mellitus and hypertension, continue to disproportionately burden low- and middle-income countries. However, little research has been done to establish current practices and management of chronic disease in these settings. The objective of this study was to examine current clinical management and identify potential gaps in care of patients with diabetes mellitus and hypertension in the district of Toledo, Belize.MethodsThe study used a mixed methodology to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…A few studies in our review reported a low prevalence of diabetes among some indigenous populations in LatAm [55,74,82], in parallel to some previous reports [283][284][285][286] about other indigenous groups in the region and in contrast with the higher prevalence of diabetes among American Indians in the USA [287] and the First Nations in Canada [288]. However, other studies in our review and in the current literature have documented elevated diabetes prevalence or risk among indigenous and other socioeconomically disadvantaged ethnic groups [48,50,73,76,77,83,90,91,166,[289][290][291][292][293]. Some of the diabetes prevalence studies included in our review focused on or mentioned participants from indigenous groups [35,48,50,74,83] and other underrepresented groups (e.g., Garifuna, Afro-Panamanian, Afro-Peruvian, Afro-Ecuadorian) [55,76,90,91,166].…”
Section: Indigenous and Other Ethnic Underserved Populationssupporting
confidence: 88%
See 1 more Smart Citation
“…A few studies in our review reported a low prevalence of diabetes among some indigenous populations in LatAm [55,74,82], in parallel to some previous reports [283][284][285][286] about other indigenous groups in the region and in contrast with the higher prevalence of diabetes among American Indians in the USA [287] and the First Nations in Canada [288]. However, other studies in our review and in the current literature have documented elevated diabetes prevalence or risk among indigenous and other socioeconomically disadvantaged ethnic groups [48,50,73,76,77,83,90,91,166,[289][290][291][292][293]. Some of the diabetes prevalence studies included in our review focused on or mentioned participants from indigenous groups [35,48,50,74,83] and other underrepresented groups (e.g., Garifuna, Afro-Panamanian, Afro-Peruvian, Afro-Ecuadorian) [55,76,90,91,166].…”
Section: Indigenous and Other Ethnic Underserved Populationssupporting
confidence: 88%
“…However, other studies in our review and in the current literature have documented elevated diabetes prevalence or risk among indigenous and other socioeconomically disadvantaged ethnic groups [48,50,73,76,77,83,90,91,166,[289][290][291][292][293]. Some of the diabetes prevalence studies included in our review focused on or mentioned participants from indigenous groups [35,48,50,74,83] and other underrepresented groups (e.g., Garifuna, Afro-Panamanian, Afro-Peruvian, Afro-Ecuadorian) [55,76,90,91,166]. However, a few studies have evaluated diabetes care, prevalence, and/or prevention of macro-or microvascular complications, diabetes management interventions, other health care needs and access to health care among indigenous populations [241,244,246,[294][295][296][297][298][299][300][301][302], and none on the other groups (that we could identify through our search).…”
Section: Indigenous and Other Ethnic Underserved Populationsmentioning
confidence: 55%
“…Also, our study showed that the mean FBG level was high for diabetic patients meaning glycaemic control was poor among diabetic patients even though they were taking anti-diabetic medicines. Our findings were consistent with those in a study by Dekker et al which showed that inadequate glycaemic control was present in 74% of all diabetic patients [15]. Additionally, a study by Nepal et al conducted in Nepal revealed that among 89 type 2 diabetic respondents only 27 (30.34%) had normal FBG level [16].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding “knowledge” (30 studies) [ 27 , 29 – 31 , 34 , 35 , 38 , 39 , 41 , 43 , 46 , 50 52 , 58 , 62 , 65 , 67 , 70 – 73 , 75 , 80 86 ], the authors recognised the importance of both patient and professional’s knowledge. Lack of professional knowledge was identified as a factor associated with miscommunication and poor management of the side effects.…”
Section: Resultsmentioning
confidence: 99%